2017
DOI: 10.1159/000478999
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Involvement of the Sonic Hedgehog Signaling Pathway in Gastric Adenocarcinoma of Fundic Gland Type and Conventional Gastric Adenocarcinoma

Abstract: Background/Aims: Gastric adenocarcinoma of fundic gland type (GAFG), which is a rare variant of gastric cancer, is reportedly associated with both Wnt/β-catenin signaling activation and guanine nucleotide binding protein, alpha stimulating complex (GNAS) mutations. This study aimed to elucidate potential roles of the Sonic hedgehog (Shh) signaling pathway in GAFG. Methods: We performed immunostaining for β-catenin and Shh signal-associated proteins, including Patched (Ptch), Smoothened (Smo), and Glioma-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Smo is a transmembrane protein that can activate the intracellular signaling pathway. After the transcription factor (Gli) in the cytoplasm is activated, it enters the nucleus and regulates the transcription of target genes [11]. Many studies have reported that the Hedgehog signaling pathway may be involved in acute inflammatory responses in tissues through the regulation of inflammatory factors [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Smo is a transmembrane protein that can activate the intracellular signaling pathway. After the transcription factor (Gli) in the cytoplasm is activated, it enters the nucleus and regulates the transcription of target genes [11]. Many studies have reported that the Hedgehog signaling pathway may be involved in acute inflammatory responses in tissues through the regulation of inflammatory factors [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Stomach cancer is seen twice more frequently in men compared to women (8). This ratio has been reported around 1,8 -2,6/1 (1,21,22). In our study, male/female ratio was found to be higher (3,3/1).…”
Section: Introductionsupporting
confidence: 49%
“…Lee et al found a higher rate of SHH in intestinal cancers and tubular adenocarcinomas compared to mucinous and signet-ring cell cancers (20). Tajima et al found that this pathway was down-regulated in fundic gland-type gastric adenocarcinomas (21). The only study reporting that overexpression of SHH was a good prognostic factor was the one performed by Kim et al (22).…”
Section: Introductionmentioning
confidence: 99%
“…The Shh signaling pathway plays crucial roles in regulating cell differentiation, adhesion, migration, transformation, and apoptosis [ 19 ]. It was found that Shh signaling was activated in many human cancers such as gastric cancer, liver cancer, breast cancer, and ovarian cancer [ 11 , 20 ]. Moreover, activation of Shh signaling was found to be highly associated with increased capacities of chemoresistance and radioresistance in human malignant tumors [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%